Theory of visual attention (TVA) in action: Assessing premotor attention in simultaneous eye-hand movements. (December 2020) - Kreyenmeier, Philipp; Deubel, Heiner; Hanning, Nina M.
Abstract: Attention shifts that precede goal-directed eye and hand movements are regarded as markers of motor target selection. Whether effectors compete for a single, shared attentional resource during simultaneous eye-hand movements or whether attentional resources can be allocated independently towards multiple target locations is controversially debated. Independent, effector-specific target selection mechanisms underlying parallel allocation of visuospatial attention to saccade and reach targets would predict an increase of the overall attention capacity with the number of active effectors. We test this hypothesis in a modified Theory of Visual Attention (TVA; Bundesen, 1990) paradigm. Participants reported briefly presented letters during eye, hand, or combined eye-hand movement preparation to centrally cued locations. Modeling the data according to TVA allowed us to assess both the overall attention capacity and the deployment of visual attention to individual locations in the visual work space. In two experiments, we show that attention is predominantly allocated to the motor targets–without pronounced competition between effectors. The parallel benefits at eye and hand targets, however, have concomitant costs at non-motor locations, and the overall attention capacity does not increase by the simultaneous recruitment of both effector systems. Moreover, premotor shifts of attention dominate over voluntary deployment of processing resources, yielding severe impairments of voluntary attention allocation. We conclude that attention shifts to multiple effector targets without mutual competition given that sufficient processing resources can be withdrawn from movement-irrelevant locations.